In memory of Stefan Czarnecki, man and scientist - ENGEL, Zbigniew; RAKOWSKI, Andrzej (Archives of Acoustics, 1983)
The outstanding Polish scientist, in the field of acoustics, Prof. Dr. Stefan CZARNECKI died in Warsaw on 1 September, 1982. Stefan CZARNECKI was born in Warsaw on 20 September, 1925. In 1945 he began his studies at the Gdańsk Technical University, to graduate in 1949 from its Electrical Engineering Department (Radiotechnology Section), achieving the M. Sc. degree with his dissertation The scaling of dynamic microphones by the reversibility method. After working a few years at the Central Laboratory of the Polish Radio and at the Warsaw Technical University, in 1953 he began to work at the Institute of Fundamental Technological Research, Polish Academy of Sciences, Warsaw.